Pengaruh posisi dan fraksi volumetrik fiber polyethylene terhadap kekuatan fleksural fiber reinforced composite (The effect of position and volumetric fraction polyethylene fiber on the flexural strength of fiber reinforced composite) - Catur Septommy; Widjijono Widjijono; Rini Dharmastiti (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: Composite resin is a combination of filler and matrix. The additional of fiber in the composite resin has a function as load-bearing in mastication. Polyethylene fiber has been used as a reinforced to receive the forces on the fixed denture fiber reinforced composite (FRC). Purpose: The purpose of this study was to determine effect of position and olumetric fraction of fibers on the flexural strength and modulus polyethylene FRC. Methods: This study used 7 groups with variations in the position and the volume of fiber. Group I, position compression volume 1 sheet; group II, 2 volume compression sheet position; group III, volume 1 sheet neutral position; group IV, neutral position volume 2 sheets; group V, position tension volume 1 sheet; group VI position tension volume 2 sheets; and group VII without fiber. Each group consisted of 6 samples and FRC rod-shaped samples with size (25 x2 x 2) mm. Samples were tested by three-point bending test with a universal testing machine. The data were analyzed by two-way Anova and LSD test continued (α = 0,05). Results: Group VI had the highest mean flexural strength than others (360.74 MPa) and group IV had the highest flexural modulus than others (3.56 GPa). The flexural strength and modulus with the variation of position or volume showed a significant differences (p<0.05), while the interaction between position and volume showed no significant difference (p>0.05). Conclusions: The position fiber on tension and additional two strips on volumetric fiber affected the increasing flexural strength and modulus of FRC.Latar belakang: Komposit merupakan gabungan filler dan matriks. Penambahan fiber pada komposit berfungsi sebagai penahan beban pengunyahan. Polyethylene fiber telah digunakan sebagai penguat dalam menerima gaya-gaya pada gigi tiruan cekat fiber reinforced composite (FRC). Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh posisi dan fraksi volumetrik fiber pada kekuatan fleksural polyethylene FRC. Metode: Penelitian ini membuat 7 kelompok sampel polyethylene FRC dengan variasi posisi dan volume fiber. Kelompok I, posisi compression volume 1 lembar; kelompok II, posisi compression volume 2 lembar; kelompok III, posisi netral volume 1 lembar; kelompok IV, posisi netral volume 2 lembar; kelompok V, posisi tension volume 1 lembar; kelompok VI, posisi tension volume 2 lembar; dan kelompok VII, tanpa fiber. Setiap kelompok terdiri atas 6 sampel dan sampel berbentuk batang FRC dengan ukuran (25x2x2) mm. Sampel diuji dengan three-point bending test dengan universal testing machine. Data dianalisis dengan two-way anova dan dilanjutkan uji LSD (α=0.05). Hasil: Rerata kekuatan fleksural kelompok VI paling tinggi (360.74 MPa) dan kelompok IV memiliki modulus fleksural tertinggi (3.56 GPa). Kekuatan dan modulus fleksural dengan variasi posisi atau volume menunjukkan perbedaan bermakna (p<0.05) sedangkan interaksi antara posisi dan volume menunjukkan perbedaan tidak bermakna (p>0.05). Simpulan: Posisi fiber pada sisi tension FRC dan penambahan volume 2 lembar fiber akan meningkatkan kekuatan fleksural FRC.